Total Quality Service of Power Marketing - Pan, Xueke (International Journal of Management and Education in Human Development, 2023)
With the rapid development and investment of clean energy such as hydropower, wind power and solar energy in China, China’s power pattern has changed greatly. The power supply has changed from the previous tight supply to surplus, and the seller’s market has changed to the buyer’s market.Under the circumstances of deepening the reform of power system and constantly changing the internal and external environment of power enterprises, this paper analyzes the situation faced by power marketing, puts forward the concept of power marketing and total quality service, and adheres to the principle of "customer first and service first". Electric power marketing is directly related to the development and growth of power supply enterprises. Therefore, it is particularly important to improve the high-quality service level of electric power marketing. In the process of electric power marketing, marketing environment, marketing methods, marketing ideas and marketers are the key factors that affect the service level of electric power marketing. The research on these factors will help electric power enterprises to improve marketing strategies and improve the service level of electric power marketing, thus improving the economic benefits of enterprises and realizing the sustainable development of enterprises.